Determinats of Customer Purchasing Decision: Price, Product, and Location - Muhammad Fuad Arisuddin; Joko Suyono; Damarsari Ratnasahara Elisabeth; Abdul Thalib Bin Bonn (LPPM of NAROTAMA UNIVERSITY, 2020)
Purpose: The purpose of this study is to analyze the effect of price, product and location on customer home purchasing decision on PT. Putra Bumi Airlangga both partially and simultaneously. Design/methodology/approach: The population in this study are all customers from PT. Putra Bumi Erlangga as many as 95 customers and sample of this study used a number of respondents who were selected by total sample or census, namely from 95 customers of PT. Putra Bumi Airlangga were selected as samples. The data analysis technique used was multiple regression analysis. Findings: The research results are: 1) Price affects customer purchasing decision of PT. Putra Bumi Airlangga, 2) Product affects customer purchasing decision of PT. Putra Bumi Airlangga, 3) Location affects customer purchasing decision of PT. Putra Bumi Airlangga, 4) Price, product and location simultaneously affect customer purchasing decision of PT. Putra Bumi Airlangga, 5) Price has the most dominant effect on customer purchasing decisions of PT. Putra Bumi Airlangga. Research limitations/implications: The number of respondent relatively small. Practical implications: Result of this research can be referred by company to increase consumer purchasing decision. Originality/value: This paper is original because there is no similar research that is conducted in PT. Putra Bumi Airlangga. Paper type: Research paper